Assessing availability and trainees’ perceptions of simulation and augmented reality in prosthodontics postgraduate education in Pakistan: a cross-sectional study - Taimur Khalid; Hassan Yaqoob; Fakeha Azhar Syed; Syed Murtaza Raza Kazmi (BMC Medical Education)
Abstract Background Simulation-based learning (SBL) and augmented reality (AR) /virtual reality (VR) are increasingly adapted and investigated globally to aid traditional teaching methods of clinical skills in several fields of clinical dentistry. This cross-sectional study was, therefore, aimed to assess the availability of such technology to Prosthodontics postgraduate trainees in Pakistan, as well as their introspective views regarding the effectiveness of adapting to simulation-based learning methods. Method Total population sampling yielded a sample of 200 participants. Weblink of a pre-validated questionnaire designed using REDCap 0.001 version 11.0.3 software was disseminated to Prosthodontics postgraduate trainees across Pakistan with the ethical review board’s approval. Trainees were inquired regarding the availability of simulation-based learning and augmented/virtual reality technology in their centres and whether they receive regular training. The authors further explored trainees’ perceptions regarding the utility and effectiveness of adopting simulation-based training in the postgraduate education system. Frequencies of categorical responses were reported. Differences in data from all provinces of Pakistan were studied with Fisher’s exact. Results Ninety completed responses were analysed with SPSS 23.0. A few trainees (n = 18, 20%) were familiar with Augmented Reality. No participant reported having Augmented Reality in their centre. Though simulation-based learning was available to 38 (42.2%) of participants across Pakistan, with differences in distribution among provinces (p = 0.001), only 24% of them received regular simulator training. Participants believe that SBL can reduce procedure-related risks (72.2%). Combining simulation-based learning with traditional teaching was favoured by 81.1% of participants. Conclusion A varied availability of SBL was observed across provinces, whereas AR was unavailable to Prosthodontics postgraduate trainees in Pakistan. Stakeholders and regulatory bodies should continually strive to incorporate technological advancements of simulation-based learning and Augmented/Virtual Reality in teaching strategies to improve Prosthodontics postgraduate students’ academic and clinical training quality. Clinical trial number Not applicable due to the cross-sectional nature of the study.